Let The Chips Fall Where They May: An Analysis of a Discussion Strategy - Burenheide, Bradley (My University, 2017)
This article explores a discussion strategy utilized in a research-based classroom to help promote participation of all students in classroom discussion. The article will establish why the strategy was employed, how best to establish the strategy, the outcomes of the strategy’s use, and finally a commentary of best practices in classroom discussions as noted from the implementation of the pedagogical strategy.
Citation: Burenheide, B. (2017). Let The Chips Fall Where They May: An Analysis of a Discussion Strategy. Manuscript, Kansas State University, Manhattan, KS.